2014
DOI: 10.1097/inf.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Vaccine-preventable Diseases in Medical Students

Abstract: Like other healthcare personnel, medical students with patient contact should be up to date with their immunizations including those specifically targeting occupational risk. Analysis from an ongoing surveillance program for medical students revealed immunization gaps in 102 (77.9%) of 131 students enrolled 2011-2013. Screening medical students' immunization records is worthwhile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In a study from Paris [35], pertussis immunization coverage was found to be 44% in medical students. In a recent study from our own institution, we found a rate of 56% [36]. Of note, all students with pertussis immunization gaps accepted Tdap during our campaign.…”
Section: Discussionmentioning
confidence: 82%
“…In a study from Paris [35], pertussis immunization coverage was found to be 44% in medical students. In a recent study from our own institution, we found a rate of 56% [36]. Of note, all students with pertussis immunization gaps accepted Tdap during our campaign.…”
Section: Discussionmentioning
confidence: 82%
“…Our data on pertussis vaccinations among German students showed comparably better and yet insufficient vaccination rates (60.5%). According to earlier studies from Germany and Switzerland based on self-reported data, 58.0% of medical students in Frankfurt [19] and 42.7% of students at the pediatric clinic at Basel University [20] reported to have received the pertussis vaccine in the past 10 years. Another study from Frankfurt reported even lower figures: Only 17.1% of the medical students reported a vaccination against pertussis in the past 10 years [23].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, health-care students are a specific sub-group of HCPs, since they share time between hospital wards and universities, which are often overlooked in immunization programs [ 55 ]. Several studies show that health-care students have significant immunity gaps and low immunization coverage rates against VPDs, which reflect immunization gaps during childhood or adolescence and the fact that they are not identified as HCPs by occupational medicine services in health-care facilities [ 55 , 56 , 57 , 58 , 59 ].…”
Section: Immunity Status Of Hcpsmentioning
confidence: 99%